Outcome measurement in cognitive neurorehabilitation - Lincoln, Nadina; das Nair, Roshan (Cambridge University Press, 2010)
Introduction: The aim of this chapter is to consider the criteria for selecting outcome measures for evaluating the effects of cognitive neurorehabilitation. The International Classification of Function, Disability and Health (ICF) (World Health Organization, 2001) is used as a framework for deciding what to measure. The properties of the ideal outcome measure are discussed. Examples of outcome measures commonly used in clinical studies are provided and their strengths and limitations considered. The focus is on self-report measures rather than neuropsychological tests as these reflect the effect of cognitive rehabilitation on daily life.